A guide to the elements - Stwertka, Albert (New York : Oxford Univerity Press, 1996)
Presents the basic concepts of chemistry and explains complex theories before offering a separate article on each of the building blocks that make up the universe.
Includes bibliographical references and index.
Elem. School Library Collection.
Library Journal.
Wilson's Senior High School.
Young Adult
Keywords: Chemical elements -- Juvenile literature; Periodic law -- Juvenile literature; Chemical elements; Chemical elements; Periodic law